2009
DOI: 10.1136/bjsm.2009.057307
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for exercise-related acute cardiac events. A case–control study

Abstract: Prior cardiovascular disease, smoking, and a recent episode of fatigue or flu-like symptoms are associated with an increased risk of exercise-related acute cardiac events. Athletes and physicians should pay careful attention when these factors exist or occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
2
12
0
3
Order By: Relevance
“…15 Ce risque est maximal chez les patients qui, ayant un mode de vie sédentaire, font brusquement un effort violent, chez les individus ayant des antécédents de maladie cardiovasculaire et chez ceux présentant des symptômes prodromiques. 16 Bien que tout effort isolé puisse contribuer à accroître le risque relatif, le risque absolu annuel de survenue d'un événement cardiaque demeure faible et est estimé à une mort subite pour 15 000 à 18 000 personnes pratiquant une activité physique. 15 Le risque peut être diminué en prêtant attention à l'apparition de nouveaux symptômes et en n'augmentant que progressivement le niveau d'activité physique.…”
Section: Effets Bénéfiques De L'entraînement Aérobie Et Anaérobieunclassified
See 1 more Smart Citation
“…15 Ce risque est maximal chez les patients qui, ayant un mode de vie sédentaire, font brusquement un effort violent, chez les individus ayant des antécédents de maladie cardiovasculaire et chez ceux présentant des symptômes prodromiques. 16 Bien que tout effort isolé puisse contribuer à accroître le risque relatif, le risque absolu annuel de survenue d'un événement cardiaque demeure faible et est estimé à une mort subite pour 15 000 à 18 000 personnes pratiquant une activité physique. 15 Le risque peut être diminué en prêtant attention à l'apparition de nouveaux symptômes et en n'augmentant que progressivement le niveau d'activité physique.…”
Section: Effets Bénéfiques De L'entraînement Aérobie Et Anaérobieunclassified
“…15 This risk is highest among chronically sedentary patients who undertake vigorous exercise abruptly, those with a history of cardiovascular disease, and those with prodromal symptoms. 16 Despite the increased relative risk with a discrete episode of exercise, the annual absolute risk of a cardiac event is small and estimated at 1 sudden death per 15 000 to 18 000 participants. 15 Risk can be decreased by paying attention to new symptoms and gradually increasing the intensity of the physical activity.…”
Section: Benefits Of Aerobic and Anaerobic Exercisementioning
confidence: 99%
“…However, because dance training does not elicit enough stimuli to increase aerobic fitness 16 , it is much more important to keep the structure of the cardiovascular and cardiorespiratory system of the dancers strong and healthy. In addition to it's many other harmful effects on human body, smoking effects the cardiovascular and cardiorespiratory health as well 4 . It has been suggested that the intensity or severity of physical activity engaged in by the athletes the extent of strengthening of respiratory muscles with resultant increase in lung volume and capacities 15 .…”
Section: Discussionmentioning
confidence: 99%
“…It is a significant public health issue in the world and also in Turkey 3 . As a major cardiovascular risk factor smoking has a potential to increase the likelihood of exercise-induced cardiac events 4 . Some studies reported that smoking has been found to have a negative impact on musculoskeletal health 5 but others found no significant association 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation